Instrumentação, controle e operacionalização de uma unidade de reparo por atrito com capacidade de carga axial de 500 kn - Borges, Bruno Marega (2011)
This work presents the results for the instrumentation, control and operation of a friction hidro pillar processing unit with an axial load capacity of 500 kN. In this case, a pin is rotated and pressed against a block with a hole. The relative motion between the surfaces creates a metallurgical bond between the pin and block material. After its instrumentation and control, tests were carried out to evaluate the functionality of the equipment and identify the limits of its operating parameters. The following parameters were controlled: axial force, rotational speed and burn-of-length. In addition to these parameters was acquired the torque, thus allowing the calculation of heat input in the operation. Welding parameter matrices were evaluated making it possible to identify the unit operating ranges as well as the effects of the input energy on the final microstructure and mechanical properties. Moreover, it was observed that using a two-stage cycle may be an important strategy to overcome some difficulties during friction hidro pillar processing.